Genotype-environment interaction for grain iron and zinc concentration in recombinant inbred lines of a bread wheat (Triticum aestivum L.) cross - Gopalareddy, K.; Singh, Anju M.; Ahlawat, Arvind K.; Singh, Gyanendra P.; Jaiswal, Jai P. (The Indian Journal of Genetics and Plant Breeding, 2016)
A set of 306 recombinant inbred lines (RILs) along with the two parents and hitherto popular wheat variety in India, PBW 343, were evaluated in three environments over two years for grain iron (Fe) and zinc (Zn) concentration. Considerable genetic variation for both grain iron and zinc concentration exists. The environment effect was the most important source of variation for grain Fe and Zn concentration, explaining 37.42% and 57.78% of the total sum of squares respectively. Genotype-environment interaction (G x E) for Fe and Zn accounted for 29.46% and 23.24% of the total sum of squares, respectively. The magnitude of G x E interaction was relatively high. High heritabilities were observed for iron (0.81) and zinc (0.71) concentrations reflecting non-crossover type of interaction. The positive and moderately high correlation (0.677**) between Fe and Zn concentration suggest good prospect of simultaneous improvement of both the micronutrients. Additive main effects and multiplicative interaction biplot and environmental indices indicated the most favorable environment for Fe to be at Delhi, which was the second most favorable environment after Samastipur in Bihar for Zn. A poor environment for grain Fe and Zn accumulation was at Pantnagar. Four stable RILs each for grain Fe and grain Zn concentration were identified.